A novel method to measure air-immobile regions of the composting pile by inverse calculation combined with gas tracer test. (1st August 2022) - Chen, Yixiao; Qin, Haiguang; Lu, Yulan; Liu, Hongtao; Zhang, Jun
Graphical abstract: Highlights: Tracer-inverse calculation method for parameters of air-immobile regions in piles. Higher β or ω slows breakthrough and lessens peak concentration of tracer in BTCs. 39%/46% of gas pores are air-immobile regions in composting piles during two phases. New protocol predicts temporal change of O2 concentration in exhaust or matrix well. Abstract: Air-immobile regions in composting piles obstruct O2 mass transport and exacerbate the formation and emission of harmful off-gases. However, effective methods for measuring the parameters of these air-immobile regions are lacking. With quartz sand piles, this study first adjusted the circumstances of a gas tracer test (gas tracer, its injection volume, and chamber type) using the two-region model (TRM). The effects of β (proportional coefficient of gas in the air-mobile region) and ω (mass exchange coefficient) on the breakthrough curves (BTCs) of the gases were then explored. Finally, an inverse calculation method was used to measure the feature parameters of air-immobile regions in two composting piles (temperature-increasing and thermophilic phases) and estimate the O2 concentrations in different composting piles (50, 100, 200 cm whole height; layers of 50, 100, 200 cm height in a 200-cm high pile). The results showed that the optimal conditions were achieved when 100 mL helium (He) as the gas tracer and a cylinder with a height/diameter ratio of 3 as the chamber were used. With the simulating composting piles, increasing β or ω slowed breakthrough and decreased peak concentration in BTCs of a gas tracer. Tracer-inverse calculation protocol can be used to efficiently estimate the volume ratios of air-immobile regions ( φ ) and first-order mass transfer coefficient ( α ), with the values of 39%/46% and 0.001/0.006 min −1 in the composting piles during temperature-increasing /thermophilic phase. The TRM also predicted the O2 concentration in the off-gas or air-mobile/immobile regions of the temperature-increasing-phase composting piles.